2017
DOI: 10.1097/hjh.0000000000001431
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour central blood pressure is not better associated with hypertensive target organ damage than 24-h peripheral blood pressure

Abstract: TOD in hypertension is associated with BP elevation, independently of the type of measurement (office or ambulatory, central or peripheral). Central BP, even monitored during 24 h, is not better associated with TOD than peripheral BP. These results do not support a routine measurement of 24-h central BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The heart ejects blood directly into the central elastic arteries. Compared with conventional brachial pressure, several 5 but not all 6 studies suggest that central pressure is more strongly related to target organ damage and the incidence of cardiovascular complications. 7 , 8 In view of the close anatomical proximity of central arteries to the heart and the strong association of electrocardiogram (ECG) voltages with BP, 9 we considered that relating ECG voltages to peripheral and central BP might generate new insights.…”
mentioning
confidence: 99%
“…The heart ejects blood directly into the central elastic arteries. Compared with conventional brachial pressure, several 5 but not all 6 studies suggest that central pressure is more strongly related to target organ damage and the incidence of cardiovascular complications. 7 , 8 In view of the close anatomical proximity of central arteries to the heart and the strong association of electrocardiogram (ECG) voltages with BP, 9 we considered that relating ECG voltages to peripheral and central BP might generate new insights.…”
mentioning
confidence: 99%
“…With respect to 24‐hour estimators of central BP, 1 study found superiority over peripheral BP in the correlation with left ventricular mass index . However, we have previously found that both central and peripheral BP were similarly associated with TOD (cardiac, renal, or vascular), and according to our results, the association of 24‐hour central BP was no longer significant after adjusting for peripheral BP …”
Section: Discussionmentioning
confidence: 97%
“…Target organ damage (TOD) was defined as the presence of renal abnormalities, left ventricular hypertrophy, or arterial stiffness. Details on such assessments have been reported elsewhere . Briefly, renal abnormalities were defined as the presence of a reduced estimated glomerular filtration rate (eGFR), < 60 mL/min/1.73 m 2 was calculated using the chronic kidney disease‐epidemiology collaborative equation (serum creatinine measured by an enzymatic modified Jaffe reaction) or by the presence of an urinary albumin excretion ≥ 30 mg/g of creatinine (measured by turbidimetry in local laboratories according to current recommended standards and calculated as the average of 2 spot first‐morning void urine samples obtained in separate days).…”
Section: Methodsmentioning
confidence: 99%
“…For example, antihypertensive therapy can have different effects on central and peripheral systolic pressure, influencing TOD, reducing left ventricular hypertrophy (LVH), cfPWV, carotid IMT and ACR [19,21]. Another study found that central aortic blood pressure, even when monitored for 24 h with an oscillometric device for pulse wave velocity [22], had similar associations with TOD to peripheral blood pressure [23]. However, the aforementioned study did not measure cfPWV but calculated it from a single point measurement of the pulse wave in the brachial cuff [23].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that central aortic blood pressure, even when monitored for 24 h with an oscillometric device for pulse wave velocity [22], had similar associations with TOD to peripheral blood pressure [23]. However, the aforementioned study did not measure cfPWV but calculated it from a single point measurement of the pulse wave in the brachial cuff [23]. Although this measurement is not yet used to for clinical assessment of TOD, some studies are starting to show significant differences in aortic PWV between groups measured with this technique [24].…”
Section: Discussionmentioning
confidence: 99%